Prevalência de enteroparasitos em crianças hospitalizadas em Pelotas, Rio Grande do Sul, Brasil - Almeida, Isis Almeida de (2013)
Intestinal parasite infections are diseases caused by protozoa and helminth groups. They are common in developing countries and are the most frequent diseases especially among children. Although it is known that hospitalized children may be more susceptible to intestinal parasites, because they are usually neglected, few studies describe the prevalence. This study aimed to investigate the prevalence of enteric parasite infections among patients admitted to the University Hospitals Pediatric Units in the municipality of Pelotas, state of Rio Grande do Sul, Brazil, from April to December, 2012. Along with the delivery of the material for collecting feces sample, a structured questionnaire was administered to parents or guardians in order to obtain information about socioeconomic conditions of the family and how much they know about parasitic diseases. They were also given an educational material addressing the major parasitic diseases in the region. Feces samples were processed according to the techniques developed by Faust (centrifugal-flotation), Ritchie (centrifugal-sedimentation), and Baermann-Moraes. Of the 106 patients investigated, 32.1% were positive for one or more intestinal parasites. Trichuris trichiura (38.24%) and Ascaris lumbricoides (35.29%) were prevalent among helminthes. Giardia lamblia (14.7%) stood out among protozoa. Analysis of the questionnaires revealed alarming results regarding to people knowledge about parasitic diseases and the lack of parasite examination among children surveyed in this municipality. The index of parasitic diseases found in this study is a clear reflection of the lack of information behind parasitic diseases, and points to the need for implementing public policies that aim at inclusion of projects in education, including in elementary school curriculum hygiene and environmental sanitation issues, as well as fecal parasite testing in hospital routine.